Brief Report: Progression of Atherosclerosis in HIV-Infected Individuals—Prospective Data From an Asian Cohort. (1st June 2017) - Lui, Grace; Ma, Ronald C. W.; Chook, Ping; Wong, Chun-Kwok; Tam, Claudia H. T.; Chan, Michael H. M.; Lee, Shui-Shan; Wong, Rity Y. K.; Cheung, Catherine S. K.; Choi, Kin-Wing; Leung, Ping-Chung; Wong, Ka-Hing; et al.
Abstract : Background: The magnitude and risk factors of progression of atherosclerosis in Asian HIV-infected individuals were unknown. This study aimed to evaluate: (1) the rate of progression of atherosclerosis in HIV-infected individuals, and (2) metabolic and inflammatory parameters that may predict atherosclerosis progression in HIV-infected individuals in an Asian cohort. Setting: A prospective, longitudinal study was performed among adults attending an HIV Metabolic clinic in Hong Kong. Methods: Carotid intima media thickness (cIMT) was measured at baseline and 24 months. Body composition, metabolic, and inflammatory biomarkers [including homeostasis model assessment of insulin resistance, LDL (low-density lipoprotein) cholesterol particle size, high-sensitive C reactive protein, adiponectin] associated with cIMT change were analyzed; their predictive performances were estimated using receiver operating characteristic analyses. Results: Sixty-one HIV-infected individuals (mean ± SD age 49.8 ± 11.4 years, 89% men, 97% Chinese, diabetes 39%, hypertension 30%, and dyslipidemia 85%) were recruited. Annual rate of change of cIMT was +0.0075 (0.0000–0.0163) mm/yr, and 19% developed new plaque at 24 months. Two patients died during the study period, 1 because of sudden cardiac death. Using receiver operating characteristic analyses, combination of lower limb fat percentage, LDL cholesterol subclass pattern B, and lower adiponectin level, but not Framingham score, predicted greater cIMT progression in HIV-infected individuals. Conclusions: Asian HIV-infected individuals had atherosclerosis progression. Limb fat percentage, LDL cholesterol particle size, and adiponectin level may identify at-risk Asian HIV-infected individuals for early intervention.